STUDI POTENSI PEMBANGKIT LISTRIK MIKROHIDRO (PLTMH) SUNGAI CIKULUWUNG DI DESA BOGOR - Sinaga, Muktar; Marcelino, Jeremy (Universitas 17 Agustus 1945 Jakarta, 2023)
AbstractEnergy is one of the main needs in human life, but along with population growth, the availability of electrical energy, especially from fossil fuels, is decreasing and is not sufficient for small-scale electricity needs. The potential generator as an alternative to fossil energy is the dwindling renewable energy source, namely PLTMH. The availability of electricity in remote villages is sometimes of concern, so research is carried out on the Study of the Potential of the Cikuluwung River Micro-hydro Power Plant (PLTMH) in Bogor Village. This study aims to provide an overview and initial information about the potential of hydropower as a basis for planning and developing MHP. The discharge is analyzed based on the observation of the flow rate by using a current meter or buoy. From the analysis of the magnitude of the potential power generated in the research area of 1.5 kW with an ideal discharge of 0.32 m3/s, the average efficiency is 88% with a design height of 10 m. This power is large enough to meet the electrification needs of residents in the study area, which is 45 kW. The result of this research is Cross Flow turbine type with runner length 352 [mm], number of blades 18 [pieces], blade distance = 40 [mm], radial rim width = 40 [mm], turbine speed 550 [rpm] and runner length = 352 [ mm].Keywords: Clean Water, Pipelines, Pump Power.AbstrakEnergi sebagai salah satu kebutuhan utama dalam kehidupan manusia, namun seiring dengan pertambahan penduduk maka ketersediaan energi listrik terutama yang berasal dari bahan bakar fosil semakin berkurang dan tidak mencukupi untuk kebutuhan listrik skala kecil listrik. Pembangkit potensial sebagai alternatif pengganti energi fosil sumber energi terbarukan yang semakin menipis yaitu PLTMH. Ketersediaan listrik di desa-desa terpencil di kadang memprihatinkan, sehingga dilakukan penelitian tentang Studi Potensi Pembangkit Listrik Mikrohidro (PLTMH) Sungai Cikuluwung di Desa Bogor. Penelitian ini bertujuan untuk memberikan gambaran dan informasi awal tentang potensi PLTA sebagai dasar perencanaan dan pengembangan PLTMH. Debit dianalisa berdasarkan pengamatan laju aliran dengan menggunakan current meter atau pelampung. Dari analisa besarnya potensi daya yang dibangkitkan di daerah penelitian sebesar 1,5 kW dengan debit ideal 0,32 m3/det, efisiensi rata-rata 88% dengan tinggi rencana turun 10 m. Kekuatan ini cukup besar untuk memenuhi kebutuhan elektrifitas warga di wilayah studi yaitu sebesar 45 kW. Hasil penelitian diperoleh tipe turbin Cross Flow panjang runner 352 [mm], jumlah sudu 18 [buah], jarak sudu = 40 [mm], lebar radial rim = 40 [mm],kecepatan turbin 550 [rpm] dan panjang runner = 352 [mm].Kata Kunci : Air Bersih , Jaringan Pipa , Daya Pompa.